STABILITY OF SMOKING STATUS IN THE U.S. POPULATION: A LONGITUDINAL INVESTIGATION - Weinberger, Andrea H. (2014)
AIMS: To determine smoking transitions in a representative sample of United States (U.S.) adults. DESIGN: Longitudinal study using data from the National Epidemiologic Survey on Alcohol and Related Conditions (Wave 1, 2001–2002; Wave 2, 2004–2005). SETTING: The general U.S. adult population. PARTICIPANTS: 33,309 adults (54% female) classified as Wave 1 Current Daily, Current Non-Daily, Former Daily, Former Non-Daily, or Never Smokers. MEASUREMENTS: Smoking transitions were determined from Wave 1 and Wave 2 data. FINDINGS: Smoking status remained stable for the majority of current daily (79.8%), former daily (95.8%), former non-daily (96.3%), and never (97.1%) smokers. Among current non-daily smokers, 54.5% quit smoking while 22.5% increased to daily smoking. Current daily smokers who were older (30–44, OR=0.62; 95% CI=0.49–0.87; 45+, OR=0.75; 95% CI=0.61–0.93) and unmarried (OR=0.80, 95% CI=0.66–0.96) were less likely to report smoking cessation. Current daily smokers who were Hispanic (OR=2.15, 95% CI=1.65–2.81) and college educated (OR=1.27, 95% CI=1.05–1.53) were more likely to report smoking cessation. Relapse in former daily smokers was greater in women (OR=1.44, 95% CI=0.27–0.74) and lower in older adults (OR=0.44; 95% CI=0.27–0.74). Smoking initiation occurred less in women (OR=0.65; 95% CI=0.49–0.87) and Hispanic adults (OR=0.57; 95% CI=0.36–0.91) and more in unmarried adults (OR=1.84; 95% CI=1.09–2.44) and adults with less education (OR=1.63; 95% CI=1.09–2.44). CONCLUSIONS: From 2001 to 2005, smoking status was extremely stable in the United States population. Specific gender, race, and educational groups need increased prevention and intervention efforts.